Sentinel lymph node biopsy and axillary dissection in breast cancer: results in a Latina population. (October 2015) - Dunstan, Jorge; Castañeda, Carlos; Abugattas, Julio; Cotrina, Jose; Castillo, Miluska; Villegas, Valeria; Dolores-Cerna, Ketty; Belmar-Lopez, Carolina; Guerra, Henry; Gomez, Henry; Vidaurre, Tatiana
Aim: we aim to evaluate accuracy of sentinel node (SN) in biopsy breast cancer (BC).Patients & methods: We reviewed 1259 early cases who underwent SN biopsy between 1996 and 2010.Results: Median age was 52 years; and 48.9, 39.7, 68.4 and 12.1% had T2, HG-III, ER + and HER2 +++, respectively. Median SN was two nodes, 34.3% had SN + and 41.6% went to axillary dissection (AD). SN-positive is associated with AD-positive nodes (p < 0.001). Number of SN-positive were related to number of AD-positive nodes (p < 0.001). Factors predicting AD-positive nodes in the SN-positive group were lymphovascular invasion (p = 0.016) and HG III (p = 0.041). Axillary recurrence was similar in those with or without AD nodes (0.0136 vs 0.0153, p = 0.8023).Conclusion: The SN predicts AD involvement and offers a low rate of axillary recurrence in our Latina population.